Housing adequacy and child outcomes in early and middle childhood - James Laurence; Helen Russell; Emer Smyth (The Economic and Social Research Institute (ESRI), 2023)
While problems in the housing system in Ireland have been under the spotlight for the last decade, relatively little attention has been paid to the experience of children and to the consequences of housing issues for child development. International research has highlighted a range of effects of poor housing on children. Poor physical housing conditions has been associated with respiratory illnesses and childhood accidents. Overcrowding has been linked to poorer educational outcomes and deprived neighbourhood conditions to socio-emotional problems. Frequent residential mobility has also been found to lead to poorer cognitive and non-cognitive outcomes. However, there is a lack of evidence on how far these findings apply in Ireland where levels of home ownership are high and levels of neighbourhood segregation are lower. This study addresses this gap. Drawing on data from the '08 Cohort of the Growing Up in Ireland study, we explore the housing conditions faced by children in early and middle childhood and the implications of these housing experiences for their cognitive, socio-emotional and health outcomes. We adopt a multi-dimensional approach to measuring housing conditions, incorporating housing tenure, suitability of accommodation, heating deprivation, neighbourhood disorder and housing mobility.
Keywords: 330; Wohnsoziologie; Wohnungswechsel; Nachbarschaft; Wirkungsanalyse; Kinder; Gesundheit; Kognition; Soziales Verhalten; Bildungsniveau; Irland